Total knee arthroplasty in patients with fixed flexion deformity - Salam, Abdus; Islam, Md Ashraful; Khan, Muhammad Zakir Hossain; Sharif, Md Sayeed Bin; Milon, Md Hafizur Rahman; Khan, Md Asmaul Hossain; Mahmud, Md Kaiser (KYAMC Journal, 2018)
Background: Fixed flexion deformity is a common accompaniment in advanced arthritis of the knee joint. Complete correction of fixed flexion deformity at the time of surgery remains challenging and technically demanding. Objectives: The purpose of our study was to assess the result of total knee replacement using a preset algorithm to assess the effect that a preoperative flexion deformity has on postoperative correction. Materials & Methods: This retrospective study reviewed severe flexion contracture of patients who underwent primary TKA and soft tissue balancing from June 2010 to July 2016. The data included preoperative, intraoperative, and postoperative evaluation at standard intervals and annual follow-up reports. Results: There were no intraoperative complications in this study. The average flexion contractures and ROM were not different between SF and MF groups (1.14 ± 0.27 vs. 1.12 ± 0.35 and 115.72 ± 15.13 vs. 118.34 ± 12.68). Conclusion: TKA can be performed successfully in knees with severe flexion contracture. KYAMC Journal Vol. 8, No.-2, Jan 2018, Page 2-7